Estudio técnico y propuesta de plan de mejora del Sistema de Alumbrado Público en la Avenida Lateral de Paso Ángel F. Rojas de la Ciudad de Loja. - Orellana Sánchez, Mario Alejandro (2023)
We focused this degree paperwork project on the proposal of one or several solutions related to the poor state of the public lighting system of the neighborhood, Avenida de Integración Barrial Angel Felicísimo Rojas, located in the city of Loja, developed as a degree project. Currently, the public lighting system has shortcomings, raising the level of insecurity for the residents of the sector, the university community (National University of Loja), and citizens in general. First, for an analysis of the current state of the avenue, we proceeded with a previous study to obtain criteria from the inhabitants of the locality in which we evidenced the failures of the public lighting system. On the other hand, A survey conducted with a sample of 115 residents of the sector showed that the citizens are not satisfied with the lighting system. Having said this, the National University of Loja is concerned about a prompt solution for the lighting system since this involves a level of insecurity for all the people who use it, with particular emphasis on the university community. Subsequently, we interviewed the entity in charge of the operation and maintenance of the public lighting system to know all the possible physical and technical characteristics of the photovoltaic panels and to conduct a survey of information related to other technologies based on this information gathered to propose one or more viable solutions. Finally, we delivered the proposed solutions for implementation in the short, medium, and long term as deemed appropriate by the entity in charge of the project. Keywords: street lighting, photovoltaic systems, solar panels, solar energy